CONTENT PRACTICES AND AUDIENCE ENGAGEMENT ON UZBEK MUSIC TV CHANNELS (BASED ON THE ADAPTED “MASKED SINGER” FORMAT) (Eureka Journal of Language, Culture & Social Change, 2026)
This article compares the approaches to content development and audience engagement of Uzbek music channels with different specialisations, using the example of their work on the same format (“Masked Singer”). It examines the differences between how the ocalizatio music channel FTV (Maska) and the non-specialised music channel Sevimli (Kim ekan) implement the same concept, based on their own distinct approaches to content management. The study refers to the original Korean version, as well as the American version, as the format models used by Uzbek TV channels during ocalization. The analysis examined the priorities for each channel, the presence of common features and differences, the concept, the structure of the episodes, the musical and visual components, the roles of the presenter and the jury, as well as models of audience engagement.
Keywords: Music television broadcasting, audience engagement, content practices, localisation, Uzbek television, FTV, Sevimli, Masked Singer